Tax Dispute Analysis of Transfer Pricing Case Study of Tax Court Decisions 2020-2023 - Aisya, Saraswati; Nuryanah, Siti (Graduate Program Magister Manajemen Pendidikan, 2024)
Tax Disputes of Transfer Pricing still become the most popular tax issue and the challenge for the MNEs' establishment worldwide. Furthermore, this study aims to continue previous research by conducting content analysis on tax court appeal decisions issued in 2020-2023. This content analysis aims to determine taxpayers' business characteristics as an essential indicator for applying the arm's length principle based on the tax court decisions for 2020-2023. The results of this study show that each type of affiliate transaction that experiences a transfer pricing tax dispute has different characteristics of taxpayers with varying conditions of industry according to the sample of the tax court decisions for 2020-2023. From now on, this study should become an information reference for tax auditors in the audit process when determining corrections to transfer pricing tax disputes, as well as encourage taxpayers to be aware of providing a comprehensive analysis of the business characteristics in preparing transfer pricing documentation.